Status of health care waste management plans and practices in public health care facilities in Gauteng Province, South Africa - Tumisang Ramodipa; Koos Engelbrecht; Ingrid Mokgobu; Daniel Mmereki (BMC, 2023)
Abstract Background Health care waste management is a challenge due to the composition of the waste generated within a health care facility, of which 85% is domestic waste, and at least 15% is hazardous waste or health care risk waste (has been in contact with blood, body fluids or tissues from humans and could cause disease). In this study, we evaluated the status quo of health care waste management plans (HCWMPs) and practices in public health care facilities in Gauteng Province, South Africa. Methods A situational analysis was employed in health care facilities (HCFs) that generated more than 20 kg (N = 42) of health care risk waste (HCRW) per day. Data was collected from officials responsible for the management of health care waste using a self-administered questionnaire whilst Chief Executive Officers/ managers of the HFCs were interviewed. Results The results showed that most (79.0%) of the health care waste officers (HCWOs) as well as management (84.6%) agreed to have HCWMPs in place. The majority (76.9%) of the HCFs have a dedicated person appointed to manage health care waste with the majority (67%) being environmental health practitioners. According to management, only 30.8% have formally appointed an integrated HCW committee. Only 11.7% of the HCWOs are guided by the Occupational Health and Safety Act to develop their HCWMPs with only 20.5% with health care waste minimisation strategies in place. Conclusion The study concluded that there is limited integration of HCWMPs as inadequate health and safety aspects, environmental pollution as well as community participation was reported. The novelty of the study is to contribute to a body of knowledge, information on the establishment of an effective health care waste management system in public health care facilities and for decision-making purposes.